(untitled) (Revista Venezolana de Salud Pública, 2018)
Obesity has become a serious health problem worldwide, being an independent risk factor for cardiovascular disease. In that sense, to evaluate the frequency of cardiac geometric alterations in obese patients with or without metabolic syndrome and other CV risk factors, a study was performed in 28 obese participants and 13 non-obese who went voluntarily to the Clinical Pharmacology Unit of the Dean of Health Sciences of UCLA who were given a questionnaire to determine other CV risk factors and had the following tests: triglycerides , Total and fractionated cholesterol, creatinine, fasting glycemia and insulin using the ELISA technique, and a transthoracic echocardiogram. The obese, sedentary population as a whole, showed significantly higher values ​​in the dimensions of the interventricular septum (SVI), posterior wall of the left ventricle (PPVI), and left atrial diameter (AI); 25% of the obese population presented concentric remodeling and 4% had eccentric hypertrophy. 32.14% of the obese presented metabolic syndrome, 64.29% dyslipidemia, 21% arterial hypertension and 28.57% smoking habits. Conclusions: Mild left ventricular morphologic alterations were found in obese patients, the presence of smoking habits in males exacerbates such alterations Keywords: Obesity, Cardiovascular Risk Factors, ventricular geometry